Clinical studies of extended-half-life recombinant FVIII products for prophylaxis in adults and children: A critical review from the physician's perspective. (June 2022) - Hermans, Cedric; Reding, Mark T.; Astermark, Jan; Klamroth, Robert; Mancuso, Maria Elisa
Abstract: This review compares the methodology of published clinical studies investigating the extended-half-life (EHL) factor VIII (FVIII) products, rFVIIIFc (efmoroctocog alfa, Elocta®/Eloctate®), BAY 94‐9027 (damoctocog alfa pegol, Jivi®), BAX 855 (rurioctocog alfa pegol, Adynovate®) and N8-GP (turoctocog alfa pegol, Esperoct®) including the phase 2/3 studies, A-LONG (NCT01181128), PROTECT VIII (NCT01580293), PROLONG-ATE (NCT01736475) and pathfinder2 (NCT01480180), respectively, and their corresponding pediatric studies and extensions. Study results are interpreted from a treating physician's perspective, translating into evidence-based, real-life use of the different EHL recombinant FVIII products for personalized prophylaxis. The similarities between the studies include methodology, objectives, study design and cohort size. The differences include duration, prophylactic dosing intervals, number of patient arms, use of control group and randomization, and treatment allocation. Comparing these studies broadens physicians' understanding of each treatment's applicability. Further evaluation of study data and future real-world studies should help physicians to confidently individualize and select treatment for each patient. Graphical Abstract: ga1 Highlights: Comparison of extended-half-life FVIII registration studies from the HCP's view. Studies differ in length, prophylaxis intervals and method of treatment allocation. Similarities include methodology, objectives, study design and cohort size. Extension studies demonstrate prophylaxis efficacy at various infusion intervals. This review may help physicians to individualize treatments for hemophilia A.